Formaldehyde measurements during OASIS Barrow field intensive Spring 2009 - Alan Fried (Arctic Data Center)
A measurement intensive campaign was carried out in Barrow, Alaska, in spring 2009 as part of the Ocean Atmosphere Sea Ice Snowpack (OASIS) program. The central focus of this campaign was the role of halogen chemistry in the Arctic. This dataset contains formaldehyde measurements. Detailed information about measurement location, tower sampling heights, estimated errors, etc. are in the data files. The data are formatted as ASCII text documents.